Case Report: Disseminated Systemic Embolism of Lipiodol After Lymphography for Plastic Bronchitis After Fontan Repair - Hubrechts, Jelena; Wåhlander, Håkan; Kjellberg-Olofsson, Cecilia; Maleux, Geert; Gewillig, Marc (Frontiers in Pediatrics, 2020)
Lipiodol-based lymphangiography is not only a diagnostic tool for visualization of lymphatic disorders such as plastic bronchitis (PB), but also aims a therapeutic effect by embolizing lymph leakages. We performed such percutaneous lymphatic embolization for PB in a Fontan patient with proven absence of right-to-left shunt, and demonstrated important lymphatic abnormalities in the mediastinum. Shortly after the procedure, the patient developed severe convulsive seizures, revealing multiple cerebral embolisms of Lipiodol. Radiological images were impressive, yet the clinical neurological outcome was favorable. Lipiodol-based lymphography in Fontan patients with plastic bronchitis should be avoided as this subgroup is more likely to have developed lympho-pulmonary venous connections which allow systemic emboli.